Von-Willebrand-Syndrom Typ 1 und Schwangerschaft - Scholz, U.; Oppermann, J.; Siegemund, A.; Schobess, R. (Hämostaseologie, 2011)
The von Willebrand-Jürgens syndrome (VWJS) type 1 is a common hereditary bleeding disorder with a bleeding tendency located especially in the mucous membranes. Women suffering from VWJS type 1 show menorrhagia and prolonged postoperative bleedings. During pregnancy the clinical presentation varies by the increase of the von Willebrand factors.In this article the laboratory findings and the clinical presentation of patients with VWJS during pregnancy was examined. The necessity of interventions during pregnancy and at the time of delivery was under consideration.
Keywords: von Willebrand disease type 1; pregnancy; bleeding